Низько хилимо голови.... - Процюк, Х. (Український визвольний рух, 2015)
Публікація містить текст виступу Ярослава Дашкевича у 1994 р. на академії, присвяченій 125-літтю від дня народження начального вождя Української Галицької Армії, генерала Мирона Тарнавського. The article contains the speech held by Yaroslav Dashkevych in 1994 at the academy, dedicated to the 125th anniversary since birth of Myron Tarnavskyi, the Commander-in-Chief of Ukrainian Galician Army.